Biogas Technology from Organic Waste and Its Implications for Public Health in Indonesia - Ramadhan Tosepu; Sayidatul Anam; Wa Harji; Wa Ode Hafiza Rahman (Journal of Epidemiology and Health Science, 2026)
Background: Usage waste organic as source energy renewable is one of the solution For overcome problem energy and environment in Indonesia. The source of biogas comes from from dirt animals, waste agriculture and waste from industry food like know, have potential big For support transition to clean and sustainable energy.​ Objectives This aim For evaluate opportunities, obstacles, and impacts biogas technology against health public with use approach review library systematic. Method: Method applied is Systematic Literature Review (SLR) on various article published scientific papers between 2021 to 2025, using reference from Google Scholar and ResearchGate. Results: Analysis results show that the use of biogas provides benefits double, namely reduce pollution environment and offers source energy more alternatives​ affordable. The use of biogas can also lower greenhouse gas emissions glass as well as reduce risk diseases caused by pollution​ air from material burn traditional. However, the development technology This Still face challenge like limitations infrastructure, investment high start, as well as low level socialization technical in society. Conclusion: Biogas technology has significant potential​ as source energy renewable and environmentally friendly environment and support health society, as long as supported by policies, education, and strengthening capacity public. Keywords: Biogas, Waste Organic, Technology, Implications, Public Health